Identification of a Novel Mitochondrial tRNA Mutation in Chinese Family with Type 2 Diabetes Mellitus - Li X; Shang J; Li S; Wang Y (Dove Medical Press, 2024)
Xing Li, Jinyao Shang, Shuang Li, Yue Wang Department of Endocrinology, Ordos Center Hospital, Ordos, Inner Mongolian, 017010, People's Republic of ChinaCorrespondence: Xing Li, Department of Endocrinology, Ordos Center Hospital, Sudu Street No. 6, Kangbashi District, Ordos, Inner Mongolian, 017010, People's Republic of China, Tel/Fax +86-0477-8167761, Email doctorlixing@sina.comBackground: Mutations in mitochondrial tRNA (mt-tRNA) could be the origin of some type 2 diabetes mellitus (T2DM) cases, but the mechanism remained largely unknown.Aim: The aim of this study was to assess the impact of a novel mitochondrial tRNACys/tRNATyr A5826G mutation on the development and progression of T2DM.Methods: A four-generation Han Chinese family with maternally inherited diabetes underwent clinical, genetic and biochemical analyses. The mitochondrial DNA (mtDNA) mutations of three matrilineal relatives were screened by PCR-Sanger sequencing. Furthermore, to see whether m.A5826G mutations affected mitochondrial functions, the cybrid cell lines were derived from three subjects with m.A5826G mutation and three controls without this mutation. ATP was evaluated by luminescent cell viability assay, mitochondrial membrane potential (MMP), and reactive oxygen species (ROS) were determined by flow cytometry. The student's two-tailed, unpaired t-test was used to assess the statistical significance between the control and mutant results.Results: The age at onset of diabetes in this pedigree varied from 40 to 63 years, with an average of 54 years. Mutational analysis of mitochondrial genomes revealed the presence of a novel m.A5826G mutation. Interestingly, the m.A5826G mutation occurred at the conjunction between tRNACys and tRNATyr, a very conserved position that was critical for tRNAs processing and functions. Using trans-mitochondrial cybrid cells, we found that mutant cells carrying the m.A5826G showed approximately 36.5% and 22.4% reductions in ATP and MMP, respectively. By contrast, mitochondrial ROS levels increased approximately 33.3%, as compared with the wild type cells.Conclusion: A novel m.A5826G mutation was identified in a pedigree with T2DM, and this mutation would lead to mitochondrial dysfunction. Thus, the genetic spectrum of mitochondrial diabetes was expanded by including m.A5826G mutation in tRNACys/tRNATyr, our study provided novel insight into the molecular pathogenesis, early diagnosis, prevention and clinical treatment for mitochondrial diabetes.Keywords: type 2 diabetes, m.A5826G, tRNACys/tRNATyr, mitochondrial dysfunction